Efficacy of Curcumin-Chitosan-Based in Glazing of Cooked Shrimp and in Coating of Dry-salted Shrimp to Extend Product Shelf-life during Preservation - N. P. Minh (Journal of Global Pharma Technology, 2016)
Chitosan has a wide range of potential applications in food science. It’s one of the best edible and biologically safe preservative coatings for different types of foods owing to its biochemical and biodegradable property, non toxicity, film-forming, antimicrobial action. Curcumin is one of the few promising natural products with a variety of therapeutic effects. Our present research demonstrated a new edible coating formula by combining chitosan 1.5% with different curcumin concentration (0.01%, 0.02%, 0.03%, 0. 04 %). This research was conducted from 2018 to 2019 in the scientific laboratory of Mekong  University. Results revealed that the chitosan-based coating layers (1.5 %) emdeded with curcumin (0.03%) could maintain the shrimp quality in glazing of cooked frozen shrimp as well as coating of dry-salted shrimp during storage. Curcumin played an important role as antioxidant in making chitosan-based film. Nontoxic, non-pollution biodegradability, surface barrier, biocompatibility, and edibility are some benefits of edible curcumin-chitosan-based coatings over plastic bags. It has been shown that it’s significantly improved the quality and increased the shelf-life of shrimp product. The improvement in the product quality is achieved through inactivation of microbial growth, reduction of lipid oxidation and enhancement of sensory characteristic.Keywords: Shrimp, Curcumin, Chitosan, Coating, Shelf-life, Lipid Oxidation, Microbial growth, Sensory characteristic.